INTEGRASI TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM PEMBELAJARAN - Muhammad Yaumi (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2011)
This article aims at comprehensively assessing the extent to which the role of information and communication technology in supporting learning process and integration model is offered by considering various opportunities and constraints faced in the imple-mentation of innovation diffusion. The use of Internet-based infor-mation communications technology such as Electronic Mail (E-mail), HP, Digital Cameras, MP3 Players, Web Sites, Wikipedia, YouTube, blogging, and podcasting are proven to be a source of learning and they are very important to be integrated. The integration of the infor-mation communication technology into learning can be applied thro-ugh innovation and diffusion strategies and ASSURE model.